Everyday behavioral and physical changes in women during the postpartum period – a qualitative approach - Salim, Natália Rejane; Santos Junior, Hudson Pires de Oliveira; Gualda, Dulce Maria Rosa (Online Brazilian Journal of Nursing, 2010)
This article seeks to add to the understanding of changes women in the puerperium experience after giving birth for the first time. This is a qualitative study in which six women whose children were born by natural birth, without untoward events in a maternity hospital accredited to the Brazilian Public Health System (Sistema Único de Saúde – SUS in Portuguese). The results show that the women experienced changes of a bodily and hormonal nature present in the post-partum period both at a physical and a psycho-social level. The women emphasized their discontentment with their self-image and their concern about perineal recovery. Thus, by learning of these women’s experiences it is essential for interventions in the promotion of health to be performed in a coherent way, in view of the demands, not yet fully addressed, that women in the postpartum period make.